A possible genetic model of the Shuangwang hydrothermal breccia gold deposit, Shaanxi Province, central China: Evidence from fluid inclusion and stable isotope. (1st November 2015) - Wang, Jianping; Liu, Jiajun; Carranza, Emmanuel John M.; Liu, Zhenjiang; Liu, Chonghao; Liu, Bizheng; Wang, Kexin; Zeng, Xiangtao; Wang, Huan
Highlights: The breccia ores of the Shuangwang gold deposit are of hydrothermal origin. Fluid boiling induced by hydrothermal explosion is critical to gold deposition. The gold deposit is explained to be related to post orogenic magmatism. Abstract: The Shuangwang gold deposit (with a gold resource of approximately 70 t Au), hosted in a NW-trending breccia belt, is located in the Fenxian-Taibai fore-arc basin in the West Qinling Orogen of central China. Four stages of ore paragenesis are identified, demonstrating mineral assemblages of ankerite–quartz–albite, quartz–albite–pyrite–ankerite, pyrite–calcite–quartz, and fluorite–dickite–gypsum, respectively. Fluid inclusions hosted in stages I, II, and III hydrothermal minerals yield homogeneous temperatures of 300–463 °C, 220–340 °C and 100–279 °C, with salinities lower than 22.7 wt% NaCl equiv. Trapping pressures estimated from CO2 –H2 O fluid inclusions show a gradual decrease from 100–170 MPa (KT8 ore body) to 17–55 MPa (KT2 ore body), corresponding to mineralization depths from 3.8–6.4 km (KT8) to 0.6–2.1 km (KT2). Hydrogen and oxygen isotopic data suggest that the ore-forming fluids evolved from metamorphic water to magmatic water, and lately meteoric water. Sulfur and carbon isotope compositions show that these fluids might have originated from interaction with the host rocks with minor additional magmatic source. Based on geochemical investigations, with combination of regional and ore deposit geology, a possible genetic model with a three-step ore-forming process is proposed. The Devonian Xinghongpu sedimentary rocks are characterized by a relatively high gold content, which might provide the initial gold source. Linear folds and faults formed during Triassic orogenic processes provided the subsequent pathways for ore-forming fluids and suitable space for gold mineralization. Postorogenic magmatic activity induced voluminous hydrothermal fluids that mixed with the basinal fluids and may have started the ore formation process. Over pressure led to hydrofracturing and the subsequent pressure drop promoted fluid boiling, which in turn resulted in abundant gold deposition. Induced by postorogenic magmatic hydrothermal activity, the Shuangwang gold deposit is considered a special type of orogenic gold deposit formed in a compression–extension transition.